2022
DOI: 10.3390/ma15051741
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Dissimilar Al/Steel Butt-Lap Joint via Ultrasonic-Assisted Friction Stir Welding

Abstract: A dissimilar AA7075/Q235 butt-lap joint was fabricated via ultrasonic-assisted friction stir welding (UaFSW), and the characteristics of the UaFSW joint were investigated systematically. The acoustoplastic effect of the ultrasonic vibration led to the softening of the materials and enhanced the material flow during welding, decreasing the volume of welding defects in the nugget zone of the UaFSW joint. With the help of ultrasonic vibration, a smooth and thin intermetallic compounds (IMCs) layer could generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the experiment, the upper and lower plates were 2024-T4 aluminum alloy and 304 stainless steel respectively, which were joined by the FSW-3LM-4012 friction stir welder (FSW, Fort Myers, FL, USA). As is known, for the butt joint by FSW, the steel plate is always put at the advancing side (AS) based on the difference in the thermal flow behaviors of these two materials [24][25][26]. For the lap joint, the aluminum alloy plate is often served as the upper plate in order to greatly decrease and even avoid the tool wear, and can be placed at the AS [30,33] or the retreating side (RS) [16,19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiment, the upper and lower plates were 2024-T4 aluminum alloy and 304 stainless steel respectively, which were joined by the FSW-3LM-4012 friction stir welder (FSW, Fort Myers, FL, USA). As is known, for the butt joint by FSW, the steel plate is always put at the advancing side (AS) based on the difference in the thermal flow behaviors of these two materials [24][25][26]. For the lap joint, the aluminum alloy plate is often served as the upper plate in order to greatly decrease and even avoid the tool wear, and can be placed at the AS [30,33] or the retreating side (RS) [16,19].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, to heighten the loading capacity of Al/steel FSW joints, the assisted welding process has gradually become a research hotspot in addition to the optimization of process parameters such as welding speed, rotating velocity, and so on [21][22][23]. The ultrasonic-assisted process has been successfully used in friction stir butt welding [24][25][26] and friction stir spot welding [27][28][29], and some researchers have also used ultrasonicassisted FSLW (UAFSLW) to join aluminum to steel [5,[29][30][31]. Hong et al [29] studied the UAFSLW joint of 6061 aluminum alloy and 301L steel and showed that the excessive growth of the Al-Fe IMC layer in the weld core region of the joint was suppressed by the stirring action of the welding tool and the ultrasonic vibration; the average thickness of the IMCs was reduced from 10 µm in the FSLW joint to 6 µm in the UAFSLW joint, and the 16.5 kN tensile load of UAFSLW joint was 27.9% higher than the traditional FSLW joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent the formation of IMCs and enhance the overall quality of the joint, certain researchers have suggested incorporating ultrasonic energy into the FSW process as a supplementary form of energy. Consequently, they have developed multiple techniques for ultrasonic vibration-assisted FSW [15][16][17][18][19]. Several research studies show that ultrasonic vibration can enhance material flow in the weld nugget zone (WNZ), prevent the growth of intermetallic compounds (IMCs), and enhance joint properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various welding techniques, such as the diffusion bonding, ultrasonic joining, and friction stir welding (FSW), have been proposed to improve welding quality [6,7]. In particular, as a solid-state joining technique, FSW generates lower welding heat input and can restrict the excessive growth of the IMC layers [8], showing great potential for fabricating high-quality Al/steel joints.…”
Section: Introductionmentioning
confidence: 99%